HKS Misinfo Review 2020
DOI: 10.37016/mr-2020-37
|View full text |Cite
|
Sign up to set email alerts
|

Misinformation more likely to use non-specific authority references: Twitter analysis of two COVID-19 myths

Abstract: This research examines the content, timing, and spread of COVID-19 misinformation and subsequent debunking efforts for two COVID-19 myths. COVID-19 misinformation tweets included more non-specific authority references (e.g., “Taiwanese experts”, “a doctor friend”), while debunking tweets included more specific and verifiable authority references (e.g., the CDC, the World Health Organization, Snopes). Findings illustrate a delayed debunking response to COVID-19 misinformation, as it took seven days for debunkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Indeed, extensive research has shown how information dissemination through social media creates an abundance of information accuracy challenges. [55][56][57][58]…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, extensive research has shown how information dissemination through social media creates an abundance of information accuracy challenges. [55][56][57][58]…”
Section: Discussionmentioning
confidence: 99%
“…First, we think that it is important to consider whether people are receiving information directly from health experts like scientists, the CDC (Centers for Disease Control and prevention), the WHO, and doctors/experts online. As primary sources, these should be the most reliable sources of information about the pandemic, and research suggests that people who engage in debunking behavior on Twitter are more likely to cite specific and verifiable authorities like the CDC or WHO than those who are sharing misinformation (McGlynn et al, 2020). In general, we argue that people who report relying on more reliable information (in this case, health experts) should be (a) more likely to correct others, and (b) be less likely to be corrected themselves (H2).…”
Section: Sources Of Informationmentioning
confidence: 99%
“…Misinformation and authority reference. Authority reference is defined as referencing an individual or organization that possesses knowledge in a related field (McGlynn et al, 2020). Reference is an important message cue derived from the post's content.…”
Section: Misinformation and Feature Characterizing: How To Detect It?mentioning
confidence: 99%
“…McGlynn et al (2020) examined the difference in authority reference usage between COVID-19 misinformation tweets and debunking tweets. According to their study, misinformation tweets were more likely to use non-specific authority references, while debunking tweets used more specific or verifiable authority references (McGlynn et al, 2020). Hence, we propose our second research question as follows:…”
Section: Misinformation and Feature Characterizing: How To Detect It?mentioning
confidence: 99%